2020
DOI: 10.1007/s13205-020-02442-8
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of potential prebiotic effects of a freeze-dried juice from Pilosocereus gounellei (A. Weber ex K. Schum. Bly. Ex Rowl) cladodes, an unconventional edible plant from Caatinga biome

Abstract: This study evaluated in vitro the potential prebiotic effects of a freeze-dried juice extracted from cladodes of Pilosocereus gounellei (A. Weber ex K. Schum.) Bly. Ex Rowl, an unconventional edible plant from Brazilian Caatinga biome and popularly known as xique-xique. Prebiotic effects of freeze-dried xique-xique cladode juice (XCJ, 20 g/L) were evaluated by measurements of prebiotic activity scores and stimulatory effects on growth and metabolic activities of probiotic Lactobacillus acidophilus LA-05, L. ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…The control formulation (CB) had higher acidity when compared to other beverage formulations (p < 0.05). This variation could be attributed to the higher concentration of passion fruit juice in CB, since it is a more acidic juice with a pH of approximately 2.8, while xique-xique cladode juice has a pH of approximately 5.0, as reported by previous studies [18,35]. The increasing acidity found during the measured refrigeration storage period could be caused by degradation of polyphenols in beverage formulations over time [9].…”
Section: Physical and Physicochemical Characteristics Of Beveragessupporting
confidence: 58%
See 3 more Smart Citations
“…The control formulation (CB) had higher acidity when compared to other beverage formulations (p < 0.05). This variation could be attributed to the higher concentration of passion fruit juice in CB, since it is a more acidic juice with a pH of approximately 2.8, while xique-xique cladode juice has a pH of approximately 5.0, as reported by previous studies [18,35]. The increasing acidity found during the measured refrigeration storage period could be caused by degradation of polyphenols in beverage formulations over time [9].…”
Section: Physical and Physicochemical Characteristics Of Beveragessupporting
confidence: 58%
“…Previous studies have also found glucose and fructose in xique-xique cladode juice (0.28 ± 0.05 g/100 g and 0.21 ± 0.06 g/100 g, respectively) [ 18 ] and passion fruit juice (1.41 ± 0.01 and 1.46 ± 0.01 g/100 g, respectively) [ 38 ], which have shown that xique-xique cladode juice has a slightly lower sugar content than passion fruit juice. Glucose and fructose contents found in the formulated beverages could be attributed to the combination of xique-xique cladode and passion fruit juices, as well as to other ingredients used in their preparation, especially sugar cane syrup.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…These effects are indicative of potential prebiotic properties. These stimulatory effects could be linked particularly by the contents of soluble fibers present in the juice (Ribeiro et al, 2020).…”
Section: Resultsmentioning
confidence: 99%